Serum Homocysteine and Atrial Fibrillation Recurrence after Catheter Ablation: A Meta-Analysis of 11 Cohort Studies Involving 2147 Patients - Li, Biao; Zeng, Fang; Zhao, Qiang (Hormone and Metabolic Research, 2024)
The relationship between serum homocysteine (Hcy) levels and atrial fibrillation (AF) recurrence following catheter ablation remains unclear. This meta-analysis aims to investigate this association. Comprehensive searches in PubMed, Web of Science, Embase, Wanfang, and China National Knowledge Infrastructure (CNKI) databases identified relevant studies published up to May 25, 2024. Cohort studies that measured pre-ablation serum Hcy levels and reported AF recurrence post-ablation were included. Data were analyzed using random-effects models by incorporating the potential influence of heterogeneity, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated for the association between serum Hcy levels and AF recurrence. Eleven retrospective cohort studies involving 2147 patients with AF who underwent catheter ablation were analyzed. Higher pre-ablation serum Hcy levels were associated with an increased risk of AF recurrence (OR for per 1 μmol/l increment of Hcy: 1.22, 95% CI: 1.17 to 1.28, p<0.001; I²=0%). Additionally, studies that categorized Hcy levels also found a higher risk of AF recurrence in patients with elevated Hcy (OR for patients with a high versus a low serum Hcy: 2.75, 95% CI: 2.02 to 3.75, p <0.001; I²=0%). Funnel plots and Egger’s regression test indicated low risks of publication bias. In conclusions, elevated pre-ablation serum Hcy levels are significantly associated with an increased risk of AF recurrence post-catheter ablation. These findings suggest that Hcy could be a valuable biomarker for predicting AF recurrence and may inform pre-ablation risk stratification. Further prospective studies are warranted to confirm these results.
Keywords: homocysteine; atrial fibrillation; catheter ablation; recurrence; meta-analysis